2(4x-1)+2(x+2)=x+7+4x+4+4x+6

Simple and best practice solution for 2(4x-1)+2(x+2)=x+7+4x+4+4x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x-1)+2(x+2)=x+7+4x+4+4x+6 equation:


Simplifying
2(4x + -1) + 2(x + 2) = x + 7 + 4x + 4 + 4x + 6

Reorder the terms:
2(-1 + 4x) + 2(x + 2) = x + 7 + 4x + 4 + 4x + 6
(-1 * 2 + 4x * 2) + 2(x + 2) = x + 7 + 4x + 4 + 4x + 6
(-2 + 8x) + 2(x + 2) = x + 7 + 4x + 4 + 4x + 6

Reorder the terms:
-2 + 8x + 2(2 + x) = x + 7 + 4x + 4 + 4x + 6
-2 + 8x + (2 * 2 + x * 2) = x + 7 + 4x + 4 + 4x + 6
-2 + 8x + (4 + 2x) = x + 7 + 4x + 4 + 4x + 6

Reorder the terms:
-2 + 4 + 8x + 2x = x + 7 + 4x + 4 + 4x + 6

Combine like terms: -2 + 4 = 2
2 + 8x + 2x = x + 7 + 4x + 4 + 4x + 6

Combine like terms: 8x + 2x = 10x
2 + 10x = x + 7 + 4x + 4 + 4x + 6

Reorder the terms:
2 + 10x = 7 + 4 + 6 + x + 4x + 4x

Combine like terms: 7 + 4 = 11
2 + 10x = 11 + 6 + x + 4x + 4x

Combine like terms: 11 + 6 = 17
2 + 10x = 17 + x + 4x + 4x

Combine like terms: x + 4x = 5x
2 + 10x = 17 + 5x + 4x

Combine like terms: 5x + 4x = 9x
2 + 10x = 17 + 9x

Solving
2 + 10x = 17 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
2 + 10x + -9x = 17 + 9x + -9x

Combine like terms: 10x + -9x = 1x
2 + 1x = 17 + 9x + -9x

Combine like terms: 9x + -9x = 0
2 + 1x = 17 + 0
2 + 1x = 17

Add '-2' to each side of the equation.
2 + -2 + 1x = 17 + -2

Combine like terms: 2 + -2 = 0
0 + 1x = 17 + -2
1x = 17 + -2

Combine like terms: 17 + -2 = 15
1x = 15

Divide each side by '1'.
x = 15

Simplifying
x = 15

See similar equations:

| 3.03(2w+4.3)=-20.07 | | 2p^2+14p+12=0 | | 3p^2+14p+12=0 | | -4=-7+w | | 8-5x=8-2x | | -6(12-15)+2x^3= | | 2w+2.5=0.5w | | 5x+2-3x=14 | | 2x^2+23x-8=0 | | 3x+(2x+6)= | | 9(z-6)= | | 18x+2=x+8+x-6 | | 17(x+3)=6(x+7)+31 | | 3x(-4)+(52+-4*2)-(-9.82)= | | 8(q+9)= | | -4(5p+4)-44=3(2p+6) | | 4x-11y=3x+7 | | -8(y+4)=-7y-5 | | -4(5t-4)+8t=5t-2 | | 6n-7+8n+2=23 | | 3-7n+5n=32-67 | | Cos(x)-2x=0 | | -53+10y+6=5(3y-4)-7 | | 12(y+4)=4(2y+1)+4y | | 3x(-4)+(52+-4*2)= | | 8a+6-8a+7= | | 30=3(y+4)-6y | | b^2-10b-45=0 | | -2(5t-5)+6t=5t-6 | | x^1=.04 | | -5(y+6)(-y-2)=0 | | 3*(-4)+(52+-4*2)= |

Equations solver categories